Remote sensing of mercury sodium exospheric patterns in relation to particle precipitation and interplanetary magnetic field - Stefano Orsini; Valeria Mangano; Anna Milillo; Alessandro Mura; Alessandro Aronica; Elisabetta De Angelis; Adrian Kazakov; Stefano Massetti; Martina Moroni; Rosanna Rispoli; Roberto Sordini; Christina Plainaki; et al. (Scientific Reports)
Abstract The ground-based solar telescope THEMIS performed several observations of Mercury’s sodium exosphere in years 2011–2013, when the MESSENGER spacecraft was orbiting around the planet. Typical two-peak exospheric patterns were frequently identified. In previous studies, some specific cases of THEMIS Na two-peak observations were characterized and related to IMF conditions, during specific extreme cases, in the occasion of CME arrival. The present study aims to perform a statistical analysis of Na two-peak emissions in nominal IMF conditions at Mercury, as measured by MESSEGER. The comparison between parameters of Na two-peak exospheric patterns (relative distances and intensities) versus the IMF intensity and Z-component is analysed, demonstrating, in average conditions, the existance of a direct relationship between Na peaks distance/intensity and IMF intensity. Moreover, only when IMF is very low, the shear angle seems to detrmine the occurrence of dayside reconnection when IMF-Z is negative (similarly to the Earth’s case), whereas at higher IMF, it seems that reconnection may occur independently from shear angle. This study supports the idea that particle precipitation is a significant driver of the shaping of Na exosphere morphology, and that only when IMF intensity is particularly low, the dayside magnetospheric structure appears to be more similar to the Earth’s configuration. These results allow to better understand the way the planet reacts to IMF conditions, thus providing interesting clues for the incoming BepiColombo measurement objectives.